Assessment of serum hepcidin level and iron profile in obese patients with nonalcoholic fatty liver disease. Issue 2 (April 2018) - Shabana, Sherif S.; Kaisar, Hany H.; Hussein, Hany A.; Abdel-Hakim, Mohammed M.
Abstract : Background/aim: In nonalcoholic fatty liver disease (NAFLD) patients, it is thought that, the iron overload is a consequence of a combination of alimentary and inflammatory-driven iron loading and retention. Recent research studies have underlined the role of hepcidin in NAFLD. Increased adipose tissue expression of hepcidin is associated with inflammation in obese individuals, independent of steatosis and nonalcoholic steatohepatitis. The current study aimed at determining the value of serum hepcidin and iron profile in obese NAFLD patients. Patients and methods: This study was a case–control comparative study. Serum hepcidin and iron profile were measured in 60 obese patients (30 obese patients with NAFLD vs. 30 obese patients without NAFLD as a control group). Results: NAFLD patients had significantly higher levels of alanine aminotransferase, aspartate aminotransferase, total cholesterol, triglycerides, low-density lipoprotein, and serum hepcidin than the control group ( P <0.05), in addition to increase in the iron profile levels in the NAFLD group than in the control group but with no significant difference between them. Serum hepcidin among cases showed highly statistically significant positive correlation with body weight ( r =0.489; P <0.001). Hepcidin at a cut-off value more than 43 ng/ml had 60% sensitivity and 83.33% specificity for prediction of NAFLD. Conclusion: There is an increase in serum hepcidin levels in obese patients with NAFLD with an increase of serum levels of iron and lipid profile in comparison with the control group; hence, serum hepcidin may be a good predictor and a noninvasive marker for diagnosis of NAFLD.